Iron citrate reduces high phosphate-induced vascular calcification by inhibiting apoptosis. (November 2016) - Ciceri, Paola; Elli, Francesca; Braidotti, Paola; Falleni, Monica; Tosi, Delfina; Bulfamante, Gaetano; Block, Geoffrey A.; Cozzolino, Mario
Abstract: Background and aims: High phosphate-induced vascular calcification (VC) and iron deficiency-induced anemia are two major contributors of cardiovascular morbidity and mortality in patients affected by chronic kidney disease (CKD). Since phosphate (Pi) control and iron replacement are common therapies in CKD, the aim of our study was to investigate the effect of iron on high Pi-induced VC in rat vascular smooth muscle cells (VSMCs). Methods: We treated VSMCs with 5 mM Pi and iron citrate (Fe 3+ ) to evaluate Ca deposition by Alizarin Red destaining, DNA fragmentation by ELISA, gene expression by RT-PCR and protein expression by Western blot. Results: Pretreatment with Fe 3+ prevents high Pi-induced calcium (Ca) deposition concentration-dependently, with 90.1% inhibition at 50 μM (0.716 ± 0.04 vs. 0.071 ± 0.01, OD/mg protein; Pi vs. Pi + Fe 3+, p < 0.01). We found that 50 μM Fe 3+ completely prevents high Pi-induced apoptosis measured as DNA fragmentation (1.51 ± 0.08 vs. 1.03 ± 0.06, Pi vs. Pi + Fe 3+ ; p < 0.01), through the prevention of the downregulation of the pro-survival pathway GAS6/AXL. Moreover, Fe 3+ stimulates autophagy, a protective phenomenon in VC, as demonstrated by electron microscopy and by autophagy flux detected by LC3IIβ protein expression. Finally, high Pi-induced osteoblastic differentiation is partially affected by Fe 3+, since BMP2 increase is prevented and OPN is enhanced, but RUNX2 increase and α-actin and SM22α decrease are not modified. Interestingly, the addition of Fe 3+ at different time points after Pi challenge completely blocks the progression of Ca deposition. Conclusions: In conclusion, iron citrate inhibits high Pi-induced Ca deposition by prevention of apoptosis, induction of autophagy, and partially affecting osteoblastic differentiation. Highlights: The role of iron in the development of vascular calcification is not yet completely clear. Our present findings demonstrate a consistent effect of iron in preventing and inhibiting vascular calcification progression. High Pi-induced vascular calcification is prevented by iron through prevention of apoptosis and the potentiation of autophagy.